Beam dynamics simulation with the use of macroparticle «PROTON» code in different variants of input dynamical matchers in a heavy ion high current RFQ structure - Vorobyov, I.A. (Вопросы атомной науки и техники, 2006)
Beam dynamics simulations with the use of macroparticle method were performed for two cases of input dynamical matchers for RFQ. It is done a comparison with data obtained from the envelope equations. These simulation results are in agreement with other simulation and theoretical ones.